A brief history of Lepidoptera section contributions to Zootaxa - Brown, John W.; Byun, Bong-Kyu; Kim, Da-Som (Zootaxa, 2021)
As a reviewer, John Brown received the first Lepidoptera manuscript submitted to Zootaxa in 2002. Within a year he was persuaded by a colleague to volunteer as its first Lepidoptera section editor. As submissions increased, he realized that he needed assistance, so in July 2005 he enlisted Robert Robbins (U.S. National Museum of National History), and the two editors split the submissions—Brown covered moths and Robbins butterflies. As submissions continued to grow, Robbins stepped down and Brown was again the sole editor. Owing to the ever-increasing manuscript load, in 2007 Brown submitted a proposal to several colleagues, inviting them to become Lepidoptera section editors, with the concept that the more editors there were, the fewer manuscripts each would have to handle, and their duties would include papers primarily in their area of expertise. The solicitation was successful, with four new subject editors coming on board in 2007: Lawrence Gall for macrolepidoptera families, Michael Toliver for butterflies, Jean-François Landry for microlepidoptera families, and Shen-Horn Yen for Pyraloidea and Zygaenoidea; the last two are still section editors today. Over the next 13 years, numerous editors came and went—turnover in editorship was always viewed as a positive way to involve new scientists and interject fresh ideas. From 2001 to 2020, a cumulative total of 21 scientists have served as Lepidoptera Section editors (Table 1), representing 14 different countries.